Dentine Thickness of Second Mesiobuccal Canals in First Maxillary Molars Prepared with Rotary Instruments: dentine thickness of prepared MB2 canals - Forghani, Maryam; Hamedi, Ali; Khorasani, Monireh; Moushekhian, Siavash; Kheirabadi, Nasir (Iranian Endodontic Journal, 2022)
Introduction: The purpose of this study was to evaluate the thickness of the remaining dentine wall in the danger zone of the second mesiobuccal (MB2) canals using cone-beam computed tomography (CBCT) in maxillary first molars following preparation by means of HERO 642 rotary instruments with different tapers. Methods and Materials: The study samples included twenty-five mesiobuccal roots of maxillary first molars. A two-step method was employed to prepare the MB2 canals applying HERO 642 instruments: using a 0.02 taper (step 1), and a 0.04 taper (step 2). The roots were scanned before preparation, and after each step. The thickness of the dentine wall was recorded at the CEJ level, as well as 2 mm and 4 mm below the CEJ. The repeated-measures ANOVA in conjunction with the Cochran tests were used to compare the changes in the thickness of the root canal wall. Results: There was no area with dentine thickness of <0.5 mm before preparation. A significant reduction in dentine thickness occurred following the preparation with both 0.02 and 0.04 files at all three levels compared with the pre-instrumentation values (P< 0.05). However, areas with dentine thickness of < 0.5 mm after preparation using 0.04 files were significantly more than those resulting from the application of 0.02 files both at the CEJ and 2 mm-below-CEJ points, but the differences were not significant at the 4mm-below-CEJ level. Conclusion: Within the limitations of the present in vitro study, the use of larger taper instruments in MB2 root canals of maxillary first molars increased the quantity of samples with dentine thickness less than 0.5 millimeter at the coronal level of the root canal. It was concluded that instruments with large tapers, should be used with caution in troughing or preparing such root canals to reduce the risk of strip perforation.